FGF Suppresses Poldip2 Expression in Osteoblasts. Issue 7 (15th March 2017) - Katsumura, Sakie; Izu, Yayoi; Yamada, Takayuki; Griendling, Kathy; Harada, Kiyoshi; Noda, Masaki; Ezura, Yoichi
ABSTRACT: Osteoporosis is one of the most prevalent ageing‐associated diseases that are soaring in the modern world. Although various aspects of the disease have been investigated to understand the bases of osteoporosis, the pathophysiological mechanisms underlying bone loss is still incompletely understood. Poldip2 is a molecule that has been shown to be involved in cell migration of vascular cells and angiogenesis. However, expression of Poldip2 and its regulation in bone cells were not known. Therefore, we examined the Poldip2 mRNA expression and the effects of bone regulators on the Poldip2 expression in osteoblasts. We found that Poldip2 mRNA is expressed in osteoblastic MC3T3‐E1 cells. As FGF controls osteoblasts and angiogenesis, FGF regulation was investigated in these cells. FGF suppressed the expression of Poldip2 in MC3T3‐E1 cells in a time dependent manner. Protein synthesis inhibitor but not transcription inhibitor reduced the FGF effects on Poldip2 gene expression in MC3T3‐E1 cells. As for bone‐related hormones, dexamethasone was found to enhance the expression of Poldip2 in osteoblastic MC3T3‐E1 cells whereas FGF still suppressed such dexamethasone effects. With respect to function, knockdown of Poldip2 by siRNA suppressed the migration of MC3T3‐E1 cells. Poldip2 was also expressed in the primary cultures of osteoblast‐enriched cells and FGF also suppressed its expression. Finally, Poldip2 was expressed in femoral bone in vivo and its levels were increased in aged mice compared to young adult mice. These data indicate that Poldip2 is expressed in osteoblastic cells and is one of the targets of FGF. J. Cell. Biochem. 118: 1670–1677, 2017. © 2016 Wiley Periodicals, Inc. Abstract : We found that Poldip2 mRNA is expressed in osteoblastic MC3T3‐E1 cells. As FGF controls osteoblasts and angiogenesis, FGF regulation was investigated in these cells. FGF suppressed the expression of Poldip2 in MC3T3‐E1 cells in a time dependent manner. Protein synthesis inhibitor but not transcription inhibitor reduced the FGF effects on Poldip2 gene expression in MC3T3‐E1 cells.